Contribution to the Pachylaelapidae (Acari: Mesostigmata) fauna in some parts of Guilan province of Iran - Samaneh Mojahed; Jalil Hajizadeh; Reza Hosseini; Ali Ahadiyat (Persian Journal of Acarology)
A faunistic study on the family Pachylaelapidae in forest and garden habitats from some regions in Guilan province, northern Iran, was carried out during 2015–2016. The samples were taken from soil, decaying organic matter, especially humus, rotten wood, moss and plant remains. A total of 10 species, belonging to three genera, were collected and identified, among them, Onchodellus squamosus Koroleva is newly recorded from Iran. Onchodellus and Pachylaelaps grandis Koroleva were considered as the most specious genus and the most frequent species, respectively. Some morphological characters and distributions of the species in Iran are discussed herein.